Academician Vladimir Mikhailovich Mysh (1873–1947) (on the 150th anniversary of his birth) - A. A. Kurygin; V. V. Semenov (Вестник хирургии имени И.И. Грекова)
An outstanding surgeon, scientist, teacher and organizer of healthcare, academician of the USSR Academy of Medical Sciences (1945), Honored Scientist of the RSFSR (1934), founder of the largest surgical school in Siberia, Professor Vladimir Mikhailovich Mysh was born on January 4 (16), 1873 in St. Petersburg in the family of a lawyer. He received his secondary education in a classical gymnasium and entered the Imperial Military Medical Academy, which he graduated in 1895 with honors and was left for three years to improve at the Department of Surgery under the guidance of Professor N. A. Velyaminov. In 1898, V. M. Mysh defended his doctoral dissertation on the topic: «Herniae vaginales ingvinales in childhood» and was assigned to Kaluga, where he worked as the head of the Surgical Department in a Military hospital. In 1901, he was elected by competition to the position of professor of the Department of General Surgery with Desmurgy and the study of dislocations and fractures at the Medical Faculty of Tomsk University. In 1909, V. M. Mysh became the head of the Department of Faculty Surgery of Tomsk University, which he headed until 1931, and in 1922, he concurrently headed the Department of Urology created by him. He was the first in Russia and the third in the world to perform radical surgery for alveolar echinococcosis of the liver. In 1931, Vladimir Mikhailovich together with the staff of Tomsk State Medical University moved to Novosibirsk, where he continued to head the Department of Surgery, and in 1935, took an active part in the opening of Novosibirsk Medical Institute and the creation of the Department of Faculty Surgery in it. V. M. Mysh initiated the introduction of specialized urological care in Siberia and made a very great contribution to the development of neurosurgery. Academician V. M. Mysh created the largest surgical school in Siberia, from which famous professors came out: V. S. Levit, G. M. Mukhadze, M. S. Rabinovich, S. L. Schneider, B. I. Fuchs, K. N. Cherepnin, A. G. Savinykh, V. M. Galkin. Vladimir Mikhailovich was the author and co-author of 136 scientific papers, including 11 monographs and manuals on abdominal and thoracic surgery, oncology, urology, neurosurgery, diseases of bones and joints, general and plastic surgery. He was awarded two Orders of Lenin, the Order of the Red Banner of Labor, medals «For Valiant Labor in the Great Patriotic War of 1941–1945», «For Labor Valor». Academician V. M. Mysh died on December 31, 1947 and was buried at the Zaeltsovsky Cemetery in Novosibirsk. The surgical clinic of the State Institute for Advanced Training of Doctors and the Department of Faculty Surgery of NSMU were named after V. M. Mysh. He was listed in the gallery of Honorary Professors of the Novosibirsk State Medical Academy.